A survey of routing and channel assignment in multi-channel multi-radio WMNs. (April 2016) - Qu, Ying; Ng, Bryan; Seah, Winston
Abstract: Wireless mesh networks provide cost-effective coverage and high network performance by utilising advanced radio frequency technology such as multiple channel multiple radio (MCMR). In spite of the advantages in MCMR wireless mesh networks, some wireless mesh networks still suffer from performance issues such as throughput degradation and unacceptable latency when network size increases. Existing studies focused on solving the performance issues from a single aspect such as routing or channel assignment. A major limitation of these studies is its failure to consider the interaction between routing and channel assignment which is a key factor influencing network performance. Different from the existing studies, we investigate routing and channel assignment in tandem. A new taxonomy is developed for evaluating the capabilities of current MCMR wireless mesh networks and used to organise past and ongoing research on routing and channel assignment algorithms. Our work provides a comprehensive analysis of existing studies from the interactive factors between routing and channel assignment. We aim to stimulate and guide the future research on joint design between routing and channel assignment in MCMR wireless mesh networks that can optimise network performance better than the individual solutions. Abstract : Graphical abstract: Abstract : Highlights: Survey existing routing and channel assignment algorithms (RCAA). Construct a new taxonomy for joint optimisation of RCAA. Analyse weakness and strengths of RCAA in the taxonomy. Suggest directions for optimisation in joint RCAA.